Chronic Obstructive Pulmonary Disease With Asthma-Like Features in the General Population in China - Huang, Kewu; Chung, Kian Fan; Yang, Ting; Xu, Jianying; Yang, Lan; Zhao, Jianping; Zhang, Xiangyan; Bai, Chunxue; Kang, Jian; Ran, Pixin; Shen, Huahao; Wen, Fuqiang; et al. (Frontiers in Medicine, 2022)
Background: Patients with features of both asthma and chronic obstructive pulmonary disease (COPD) are seen commonly in the clinic but less is known in the general population. We investigated the prevalence and the heterogeneity of COPD with concomitant features of asthma in Chinese adult population. Methods: COPD was defined as post-bronchodilator ratio of forced expiratory volume in 1s (FEV1) to forced vital capacity of less than the lower limits of normal. COPD with concomitant features of asthma was defined as either COPD with asthma diagnosed by self-reported physician-diagnosis or by presence of current wheeze, or as COPD with high bronchodilator response (HBR) defined as an increase in FEV1 >15% and >400 ml after bronchodilator. Results: COPD with concomitant features of asthma was found in 1.62% (95% CI 1.31-2.00) of adults (≥20 years) or in 15.2% (95% CI 13.0-17.7) of COPD patients. Compared with COPD with HBR, COPD with asthma diagnosis or wheeze were older (61.8±1.1 years vs 47.4±2.8 years, P<0.001), and with a lower post-bronchodilator FEV1%pred (68.2±2.3 vs 96.6±3.4, P<0.001). Age, smoking status, biomass use and allergic rhinitis were associated with increasing prevalence of COPD with asthma diagnosis or wheeze, and had greater impaired health status, more comorbidities and more acute exacerbations in the preceding 12 months. Conclusions: COPD with concomitant features of asthma is common in people with COPD and those with COPD with asthma diagnosis or wheeze experience worse clinical severity than COPD with HBR. These findings will help towards the definition of the asthma-COPD overlap condition.